Diseño y simulación de una máquina clasificadora por visión artificial y despulpadora de cacao - Albarracín Macías, Miguel Eduardo (2018)
This research project is focused on the design of an agricultural machine that allows us to depulping the cocoa almonds quickly and optimally by means of an artificial vision system that allows to obtain the mentioned product in a shorter time. Cocoa has been placed in the third place after sugar and coffee, this is due to the growing demand for chocolate, which is one of its most consumed derivatives in the world. Prior to the design are investigated manual and traditional methods executed in the farms to take an alternative mechanical design, in effect of the three alternatives proposed was decided to take as an example the alternative C made by a zaranda with a Constant translational Movement. This machine was designed with the help of the SOLIDWORKS software, allowing to obtain planes and dimensions suitable for its construction. In the same it was possible to perform a finite element analysis to evaluate its deformations with the loads to which it will be subjected. The design of this machine aims to open new fields in agricultural production and maximize the income of small farmers, taking advantage of the reduction of labor used in the process of pulping cocoa. Key words: Cocoa, machine, depulping process, artificial vision